Application of Boron Nitride Nanotube Interlayers for Thermal Management of 2D and 3D Printed Flexible Electronics - Wagner, Kaitlin (Université d'Ottawa | University of Ottawa, 2025)
The development of flexible printed electronics, which are compatible with low-cost fabrication techniques, lightweight and can be fabricated over large areas, enables the integration of devices into existing architectures with diverse form factors that rigid silicon-based electronics cannot accomplish. However, flexible substrates derived from thermoplastics are typically temperature sensitive and are susceptible to degradation when exposed to elevated temperatures during device fabrication and the application of high voltages during operation. To address these deficiencies, highly efficient thermal management techniques and materials that can be integrated directly into flexible electronic devices without compromising their electrical properties and performance are required. My thesis presents the development and application of thin films fabricated from boron nitride nanotubes (BNNT) as an interlayer for thermal management in printed electronic structures. I first report the efficacy of the ultra-thin BNNT interlayers to reduce heat damage caused to the substrate during intense pulsed light sintering of molecular ink traces, successfully demonstrating the fabrication of highly conductive and morphologically uniform traces. I then translate this concept towards utilizing the thermally conductive properties of the BNNT interlayer to improve heating uniformity in screen-printed flexible transparent heaters at high generated temperatures without significantly affecting trace morphology. Next, I substitute the traditional chlorinated solvent base of the BNNT dispersion for ethanol, resulting in no adverse effects to the electrical, mechanical or thermal properties of the transparent heater architecture and enabling opportunities to utilize chemically sensitive device materials. Finally, I demonstrate that the BNNT interlayer successfully dissipates mechanical and thermal stress imparted on 2D printed traces that were transformed into 3D features using thermoforming techniques. Overall, my thesis demonstrates a significant contribution to knowledge towards the development of printed electronics on temperature sensitive plastic substrates.
Keywords: Chemical Engineering; Printed Electronics; Boron Nitride Nanotubes; Thermal Management; Molecular Ink